Do cooperative systems make drivers’ car-following behavior safer? - Farah, Haneen; Koutsopoulos, Haris N. (Transportation research. Part C, Emerging technologies, 2014)
•This study investigates the Impact of I2V system on driver car-following behavior.•Instrumented vehicle was used to collect real data from the field.•Car-following models were estimated with and without the system.•Calibrated models’ comparison showed that the system harmonizes drivers’ behavior.•The calibrated models can be implemented in simulation programs. The main goal of in-vehicle technologies and co-operative services is to reduce congestion and increase traffic safety. This is achieved by alerting drivers on risky traffic conditions ahead of them and by exchanging traffic and safety related information for the particular road segment with nearby vehicles. Road capacity, level of service, safety, and air pollution are impacted to a large extent by car-following behavior of drivers. Car-following behavior is an essential component of micro-simulation models. This paper investigates the impact of an infrastructure-to-vehicle (I2V) co-operative system on drivers’ car-following behavior. Test drivers in this experiment drove an instrumented vehicle with and without the system. Collected trajectory data of the subject vehicle and the vehicle in front, as well as socio-demographic characteristics of the test drivers were used to estimate car-following models capturing their driving behavior with and without the I2V system. The results show that the co-operative system harmonized the behavior of drivers and reduced the range of acceleration and deceleration differences among them. The observed impact of the system was largest on the older group of drivers.